Isabella d'Este, marchioness of Mantua, 1474-1539 : a study of the Renaissance / by Julia Cartwright (Mrs. Ady). - Ady, Julia Mary Cartwright, -1924. (Tufts University. Tisch Library., 2015)
Volume 1 of 2.; 1 online resource (2 volumes) : frontispieces, plates, portraits, genealogical, tables.; Originally published in 1903.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University,2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.